Inventory of educational practices that favor creativity in higher education level - Eunice M. L. Soriano de Alencar; Denise de Souza Fleith (Psicologia: Reflexão e Crítica, 2004)
The purpose of this study was to construct and validate an instrument that assessed university students' perception with respect to what extent their teachers had presented behaviors and implemented educational practices that favoured the development and expression of students' creativity. The instrument was named Inventory of Educational Practices and consisted of 37 itens related to distinct dimensions of creativity. This instrument was administered to 1068 students from public and private universities. A factorial analysis was conducted and four factors were generated: Incentive to New Ideas, Climate for the Expression of Ideas, Evaluation and Methodology of Teaching, and Interest for the Student's Learning. The alpha coefficients of reliability for all factors were above .72. The results indicated that the inventory discriminates distinct dimensions of teacher behavior that are relevant to the development of creativity, being an useful instrument for researching and diagnosing educational practices.